Precursor and method for producing positive electrode active material for lithium secondary battery
Patent Information
- Application Number
- JP2023148424
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-13
- Publication Date
- 2025-03-26
AI Technical Summary
【0009】 本発明によれば、放電レート特性に優れ、初回充放電効率が高いリチウム二次電池を製造可能なリチウム二次電池用正極活物質の前駆体を提供することができる。さらにこのような前駆体を用いたリチウム二次電池用正極活物質の製造方法を提供することができる。
Smart Images

Figure 2025041245000003 
Figure 2025041245000004 
Figure 2025041245000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a precursor and a method for producing a positive electrode active material for a lithium secondary battery. [Background technology]
[0002] The positive electrode of the lithium secondary battery has a positive electrode active material for lithium secondary batteries. The positive electrode active material for lithium secondary batteries is obtained, for example, by firing a mixture of a lithium compound and a precursor. The precursor is, for example, a metal composite oxide containing a metal element other than Li.
[0003] Attempts have been made to control the crystal state of precursors as a technique for improving the battery performance of lithium secondary batteries.
[0004] For example, Patent Document 1 discloses a method for producing a positive electrode active material, which includes a step of oxidizing and roasting a nickel-cobalt-manganese composite hydroxide obtained in a coprecipitation step to obtain a nickel-cobalt-manganese composite oxide. Patent Document 1 discloses that the use of a positive electrode active material made from such a precursor as a raw material improves the initial discharge capacity and capacity retention rate of a lithium secondary battery. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP-A-2010-15959 Summary of the Invention [Problem to be solved by the invention]
[0006] As the application fields of lithium secondary batteries continue to expand, there is a demand for precursors that can be used to manufacture lithium secondary batteries with improved discharge rate characteristics and initial charge / discharge efficiency.
[0007] The present invention has been made in view of the above circumstances, and aims to provide a precursor of a positive electrode active material for a lithium secondary battery that can be used to manufacture a lithium secondary battery having excellent discharge rate characteristics and high initial charge / discharge efficiency, and a method for manufacturing a positive electrode active material for a lithium secondary battery using such a precursor. [Means for solving the problem]
[0008] An aspect of the present invention includes [1] to [9]. [1] A precursor of a positive electrode active material for a lithium secondary battery, the precursor containing at least Ni and one or more elements selected from the group consisting of Co and element M1, and satisfying the following (1) and (2): (1) In the pore size distribution calculated from the nitrogen adsorption isotherm by the Barrett-Joyner-Halenda (BJH) method, the total pore volume in the pore size range of 2 nm to 200 nm is 0.115 cm 3 / g or more 0.180cm 3 / g or less. (2) 0.84 (A is the half-width of the diffraction peak in the range of 2θ=37.5±1° in powder X-ray diffraction measurement using a CuKα radiation source, and B is the half-width of the diffraction peak in the range of 2θ=43.5±1°.) [2] The precursor according to [1], which satisfies the following (3): (3) 0.6 × 10 -3 ≦C / D 50 ≦1.6×10 -3 (C is the average pore diameter (nm) in the pore diameter distribution, and D 50 is the 50% cumulative volume particle size (μm) obtained from the volume-based cumulative particle size distribution curve measured by a laser diffraction scattering method. [3] The precursor according to [1] or [2], which satisfies the following (4): (4) 1.0×10 -3 ≦C / D 10 ≦2.5×10 -3 (C is the average pore diameter (nm) in the pore size distribution, and D 10 is the 10% cumulative volume particle size (μm) obtained from the volume-based cumulative particle size distribution curve measured by the laser diffraction scattering method.) [4] The precursor according to any one of [1] to [3], which satisfies the following (5). (5) 0.4×10 -3 ≤ C / D 90 ≤ 1.0×10 -3 (C is the average pore diameter (nm) in the pore size distribution, and D 90 is the 90% cumulative volume particle size (μm) obtained from the volume-based cumulative particle size distribution curve measured by the laser diffraction scattering method.) [5] The precursor according to any one of [1] to [4], having a BET specific surface area of 25 m 2 / g or more and 100 m 2 / g or less. [6] The precursor according to any one of [1] to [5], wherein C, which is the average pore diameter in the pore size distribution, is 8 nm or more and 20 nm or less. [7] D, which is the 50% cumulative volume particle size obtained from the volume-based cumulative particle size distribution curve measured by the laser diffraction scattering method 50 is 10 μm or more and 20 μm or less, and the precursor according to any one of [1] to [6]. [8] The precursor according to any one of [1] to [7], which satisfies the following formula (I). Ni:Co:M1 = (1 - y - z):y:z ···(I) (M1 is one or more elements selected from the group consisting of Mn, Mg, Ca, Sr, Ba, Zn, B, Al, Ga, Ti, Zr, Ge, Fe, Cu, Cr, V, W, Mo, Sc, Y, Nb, La, Ta, Tc, Ru, Rh, Pd, Ag, Cd, In, and Sn. Formula (I) satisfies 0 ≤ y ≤ 0.4, 0 ≤ z ≤ 0.5, and 0 < y + z.) [9] A method for producing a positive electrode active material for a lithium secondary battery, comprising a step of firing a mixture of the precursor according to any one of [1] to [8] and a lithium compound. [Advantages of the Invention]
[0009] According to the present invention, it is possible to provide a precursor for a positive electrode active material for a lithium secondary battery, which can produce a lithium secondary battery having excellent discharge rate characteristics and high initial charge / discharge efficiency, and further to provide a method for producing a positive electrode active material for a lithium secondary battery using such a precursor. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a schematic diagram illustrating an example of a lithium secondary battery. [Diagram 2] FIG. 1 is a schematic diagram showing the overall configuration of an all-solid-state lithium secondary battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] <Terminology> The terms used in this specification are defined as follows. The term "CAM" stands for Cathode Active Material for lithium secondary batteries. Lithium secondary batteries refer to lithium ion secondary batteries.
[0012] An expression indicating the symbol of a metal element (for example, "Ni") indicates the element, not the metal element, unless otherwise specified. In this specification, the "metal element" also includes B, which is a metalloid element.
[0013] Regarding a numerical range, for example, "1 to 10 μm" means a numerical range from 1 μm to 10 μm including the lower limit (1 μm) and the upper limit (10 μm), that is, "1 μm or more and 10 μm or less."
[0014] [Method for measuring total pore volume] The "pore size distribution" of the precursor is determined by analyzing the nitrogen desorption isotherm obtained by measuring the precursor at liquid nitrogen temperature using the Barrett-Joyner-Halenda (BJH) method. For example, the BELSORP-mini (manufactured by Microtrack BEL Co., Ltd.) can be used as a measuring device for the nitrogen desorption isotherm.
[0015] First, 5 g of the precursor is vacuum degassed at 105°C for 8 hours using a vacuum heat treatment device (BELSORP-vacII, manufactured by Microtrack-Bell Co., Ltd.). After the treatment, the amount of nitrogen adsorbed by the precursor at liquid nitrogen temperature (77K) is measured using the above-mentioned measuring device, and a nitrogen desorption isotherm is created.
[0016] The nitrogen desorption isotherm is plotted as follows: the horizontal axis is the ratio of the adsorption equilibrium pressure to the saturated vapor pressure (relative pressure (ρ / ρ0)), and the vertical axis is the amount of gaseous nitrogen adsorbed (cm) at standard temperature and pressure (STP). 3 The results are plotted as (STP) / g.
[0017] The obtained nitrogen desorption isotherm is analyzed by the BJH method to obtain the pore size distribution in the pore size range of 2 to 200 nm. The pore size distribution is calculated by dividing the differential pore volume dV by the logarithmic differential value d (logD) of the pore diameter D, and the horizontal axis represents the pore diameter (nm, logarithmic scale) and the vertical axis represents the log differential pore volume (cm 3 / g).
[0018] In the pore size distribution obtained by the above method, the total pore volume of the precursor in the pore size range of 2 to 200 nm is determined.
[0019] [Powder X-ray diffraction measurement] The powder X-ray diffraction measurement of the precursor is carried out using a powder X-ray diffraction measurement device, such as Ultima IV manufactured by Rigaku Corporation. Specifically, the precursor powder is filled into a dedicated substrate, and a Cu-Kα source is used to perform measurements under the conditions of a diffraction angle 2θ=10-90°, a sampling width of 0.02°, and a scan speed of 4° / min to obtain a powder X-ray diffraction pattern. From the obtained powder X-ray diffraction pattern, the half-width A of the diffraction peak present within the range of 2θ=37.5±1° and the half-width B of the diffraction peak present within the range of 2θ=43.5±1° are analyzed using analysis software (e.g., the integrated powder X-ray analysis software JADE), and the ratio (A / B) is calculated.
[0020] [Method of measuring average pore size] From the pore size distribution obtained by the above [Method of measuring total pore volume], the average pore size C of the precursor in the pore size range of 2 to 200 nm is obtained.
[0021] [Method of measuring particle size distribution] The particle size distribution of the precursor is determined on a volume basis and is measured using an apparatus that uses the laser diffraction scattering method as the measurement principle. Specifically, 0.1 g of the precursor powder is put into 50 ml of 0.2 mass % sodium hexametaphosphate aqueous solution to obtain a dispersion in which the powder is dispersed. Next, the particle size distribution of the obtained dispersion is measured using a particle size distribution measuring apparatus, and a cumulative particle size distribution curve on a volume basis is obtained. For example, the MT3000II (manufactured by Microtrack Bell) can be used as the particle size distribution measuring apparatus.
[0022] In the obtained cumulative particle size distribution curve based on volume, the particle size at which the cumulative volume ratio from the small particle side is 50% when the whole is taken as 100% is defined as the 50% cumulative volume particle size (D 50 (μm)), and the particle size at 10% is the 10% cumulative volume particle size (D 10 (μm)), and the 90% cumulative volume particle size (D 90 (μm).
[0023] [Method for measuring BET specific surface area] The BET specific surface area of the precursor (unit: m 2 / g) can be measured by a BET specific surface area measuring device after drying 1 g of the precursor powder in a nitrogen atmosphere at 105° C. for 30 minutes. As the BET specific surface area measuring device, for example, Macsorb (registered trademark) manufactured by Mountech Co., Ltd. can be used.
[0024] [Composition analysis] The composition of the precursor is measured by dissolving the precursor powder in hydrochloric acid and then using an ICP emission spectrometer, such as Optima 7300 (manufactured by PerkinElmer Co., Ltd.).
[0025] [Precursor evaluation method] The precursor is evaluated after a lithium secondary battery is produced by the following method.
[0026] (CAM Creation) The precursor and lithium hydroxide monohydrate powder are weighed and mixed in a molar ratio of Li / (Ni+Co+M1)=1.02 to obtain a mixture. The resulting mixture is calcined at 650°C for 5 hours in an oxygen-containing atmosphere, and then calcined at 740°C for another 5 hours to obtain a calcined product. The calcined product is mixed with pure water whose liquid temperature has been adjusted to 5°C in a ratio such that the weight ratio of the calcined product to the total amount is 50 mass% to produce a slurry. The slurry is stirred for 20 minutes and washed, then dehydrated and heat-treated at 210°C for 10 hours in a nitrogen atmosphere to obtain CAM.
[0027] (Preparation of positive electrodes for lithium secondary batteries) The obtained CAM, a conductive material (acetylene black), and a binder (PVdF) are added and kneaded in a ratio of CAM:conductive material:binder = 92:5:3 (mass ratio) to prepare a paste-like positive electrode mixture. When preparing the positive electrode mixture, N-methyl-2-pyrrolidone is used as an organic solvent.
[0028] The obtained positive electrode mixture is applied to a 40 μm thick Al foil as a current collector and vacuum dried at 150 °C for 8 hours to obtain a positive electrode for a lithium secondary battery. The electrode area of this positive electrode for a lithium secondary battery is 1.65 cm 2 Let us assume that.
[0029] (Production of lithium secondary batteries) The following operations are carried out in a glove box under an argon atmosphere. The positive electrode for lithium secondary battery prepared in (Preparation of positive electrode for lithium secondary battery) is placed on the bottom cover of a part for coin type battery R2032 (for example, manufactured by Hosen Co., Ltd.) with the aluminum foil side facing down, and a separator (porous film made of polyethylene) is placed on top of it. 300μL of electrolyte is poured here. The electrolyte is a liquid obtained by dissolving LiPF6 at a ratio of 1.0mol / L in a mixture of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a ratio of 30:35:35 (volume ratio).
[0030] Next, metallic lithium is used as the negative electrode, and the negative electrode is placed on the separator, and a lid is placed on the separator via a gasket, and the lid is crimped with a crimping machine to prepare a lithium secondary battery (coin-type half cell R2032). The lithium secondary battery thus prepared is left to stand at room temperature for 12 hours to allow the separator and the positive electrode mixture layer to be sufficiently impregnated with the electrolyte, and then used for the measurements described below.
[0031] A discharge rate test is carried out under the following conditions using the lithium secondary battery prepared in the above (Preparation of Lithium Secondary Battery).
[0032] (Discharge rate test) Test temperature: 25℃ Maximum charging voltage 4.3V, charging current 0.2CA, constant current constant voltage charging Minimum discharge voltage 2.5V, discharge current 0.2CA or 1CA, constant current discharge
[0033] Using the discharge capacity when discharged at a constant current of 0.2 CA and the discharge capacity when discharged at a constant current of 1 CA, the 1CA / 0.2CA discharge capacity ratio is calculated using the following formula (X) and used as an index of discharge rate characteristics. 1CA / 0.2CA discharge capacity ratio (%) = Discharge capacity at 1 CA / Discharge capacity at 0.2 CA × 100 (X)
[0034] When the 1CA / 0.2CA discharge capacity ratio obtained by the above method is 93.0% or more, it is evaluated as having "excellent discharge rate characteristics".
[0035] Using the lithium secondary battery prepared in the above (Preparation of lithium secondary battery), an initial charge / discharge test is carried out under the following conditions. The initial charge / discharge efficiency is calculated from the initial charge capacity and initial discharge capacity obtained in the initial charge / discharge test using the following formula (Y). First charge / discharge efficiency (%) = Initial discharge capacity (mAh / g) / Initial charge capacity (mAh / g) × 100 Formula (Y)
[0036] (Charge / discharge test conditions) Test temperature: 25℃ Maximum charging voltage 4.3V, charging current 0.2CA, constant current constant voltage charging Minimum discharge voltage 2.5V, discharge current 0.2CA, constant current discharge
[0037] When the initial charge / discharge efficiency obtained by the above method is 87.0% or more, it is evaluated as "high initial charge / discharge efficiency."
[0038] <Precursor> The precursor of this embodiment contains at least Ni and one or more elements selected from the group consisting of Co and element M1. The precursor is preferably a hexagonal compound having a layered structure. The precursor does not substantially contain Li. The precursor preferably contains Ni, Co, and an element M1, which is one or more elements selected from the group consisting of Mn, Mg, Ca, Sr, Ba, Zn, B, Al, Ga, Ti, Zr, Ge, Fe, Cu, Cr, V, W, Mo, Sc, Y, Nb, La, Ta, Tc, Ru, Rh, Pd, Ag, Cd, In, and Sn.
[0039] The precursor satisfies the following (1) and (2). (1) In the pore size distribution calculated from the nitrogen adsorption isotherm by the Barrett-Joyner-Halenda (BJH) method, the total pore volume in the pore size range of 2 to 200 nm is 0.115 to 0.180 cm 3 / g or less. (2) 0.84 (A is the half-width of the diffraction peak in the range of 2θ=37.5±1° in powder X-ray diffraction measurement using a CuKα radiation source, and B is the half-width of the diffraction peak in the range of 2θ=43.5±1°.) Each requirement will be explained below.
[0040] (1) The total pore volume of the precursor is 0.118 cm 3 / g or more is preferable, and 0.120 cm 3 / g or more. The total pore volume of the precursor is preferably 0.170 cm 3 / g or less is preferable, and 0.160 cm 3 / g or less is more preferable, and 0.157 cm 3 The total pore volume of the precursor is preferably 0.118 to 0.170 cm3 / g or less. 3 / g is preferable, and 0.120 to 0.160 cm 3 / g is more preferable, and 0.120 to 0.157 cm 3 / g is more preferred.
[0041] A precursor having a total pore volume equal to or greater than the lower limit has sufficient pores that can become reaction sites. A CAM produced using such a precursor as a raw material is likely to have sufficient reaction sites where lithium ions can be inserted during charging and desorbed during discharging, and lithium ions are likely to diffuse during charging and discharging, i.e., the internal resistance is likely to be low. This makes it easy to improve the discharge rate characteristics and initial charge / discharge efficiency of a lithium secondary battery.
[0042] On the other hand, if there are an excess of reactive sites, side reactions that deteriorate the battery characteristics are likely to occur, such as a reaction in which the electrolyte decomposes to generate gas. The CAM produced by using the precursor having a total pore volume equal to or less than the upper limit as a raw material does not have too many reaction sites, and side reactions are less likely to occur during charging and discharging, which can improve the discharge rate characteristics and initial charge / discharge efficiency of the lithium secondary battery.
[0043] (2) The A / B ratio of the precursor is preferably 0.850 or more, more preferably 0.855 or more, and is preferably 0.940 or less, more preferably 0.935 or less.
[0044] The precursor preferably satisfies the following (2)-1, and more preferably satisfies the following (2)-2. (2)-1: 0.850≦A / B≦0.940 (2)-2: 0.855≦A / B≦0.935
[0045] The above precursor has diffraction peaks within the range of 2θ=37.5±1° and within the range of 2θ=43.5±1°. The diffraction peak within the range of 2θ=37.5±1° is the X-ray diffraction peak of the (111) plane of the precursor, and the diffraction peak within the range of 2θ=43.5±1° is the X-ray diffraction peak of the (200) plane of the precursor.
[0046] In a precursor that satisfies the above condition (2), the crystals grow biased toward a specific plane direction and have anisotropy.
[0047] Through investigations by the present inventors, it has been found that the use of a CAM produced by using, as a raw material, a precursor that satisfies the above (2) improves the discharge rate characteristics and initial charge / discharge efficiency of a lithium secondary battery.
[0048] The reason for this is presumed to be as follows. In a CAM produced using a precursor that satisfies the above (2) as a raw material, lithium ions are likely to diffuse during charging and discharging, i.e., the internal resistance is likely to be low. In a lithium secondary battery using such a CAM, lithium ions are unlikely to be consumed during anything other than charging and discharging, so the initial charge / discharge efficiency is likely to be improved.
[0049] In addition, the CAM prepared using the precursor that satisfies the above (2) does not have too large anisotropy, and it is considered that the crystal planes of the primary particles that desorb lithium ions during charging and insert lithium ions during discharging are irregular throughout the CAM. As a result, there are places where lithium ions tend to move straight, and lithium ions tend to diffuse. This increases the capacity even at high discharge rates, and the discharge rate characteristics tend to improve.
[0050] The angle A of the precursor is preferably 0.51° or more, and more preferably 0.52° or more. The angle A is preferably 0.70° or less, and more preferably 0.65° or less. The angle A is preferably 0.51 to 0.70°, and more preferably 0.52 to 0.65°. The angle B of the precursor is preferably 0.50° or more, and more preferably 0.55° or more. The angle B is preferably 0.80° or less, and more preferably 0.70° or less. The angle B is preferably 0.50 to 0.80°, and more preferably 0.55 to 0.70°.
[0051] It is preferable that the precursor satisfies the following (3). (3) 0.6 × 10 -3 ≦C / D 50 ≦1.6×10 -3
[0052] C / D 50 is 0.65 × 10 -3 More preferably, 0.68×10 -3 More than or equal is preferable. C / D 50 is 1.4 × 10 -3 Less than or equal to 1.15×10 is preferable. -3 The following is even more preferable. The precursor more preferably satisfies the following (3)-1, and even more preferably satisfies the following (3)-2. (3)-1: 0.65×10 -3 ≦C / D 50 ≦1.4×10 -3 (3)-2: 0.68×10 -3 ≦C / D 50 ≦1.15×10 -3
[0053] It is preferable that the precursor satisfies the following (4). (4) 1.0×10 -3 ≦C / D 10 ≦2.5×10 -3
[0054] C / D 10 is 1.10 x 10 -3 More preferably, 1.19×10 -3 More than or equal is preferable. C / D 10 is 2.2 x 10 -3 Less than 2.0×10 is more preferable. -3 The following is even more preferable. The precursor more preferably satisfies the following (4)-1, and even more preferably satisfies the following (4)-2. (4)-1:1.10×10 -3 ≦C / D 10 ≦2.2×10 -3 (4)-2: 1.19×10 -3 ≦C / D 10 ≦2.0×10 -3
[0055] It is preferable that the precursor satisfies the following (5). (5) 0.4 × 10 -3 ≦C / D 90 ≦1.0×10 -3
[0056] C / D 90 is 0.5 x 10 -3 Above is preferable. C / D 90 is 0.9 × 10 -3 Less than 0.8×10 is preferable. -3 The following is even more preferable. The precursor more preferably satisfies the following (5)-1, and even more preferably satisfies the following (5)-2. (5)-1: 0.4×10 -3 ≦C / D 90 ≦0.9×10 -3 (5)-2: 0.5×10 -3 ≦C / D 90 ≦0.8×10-3
[0057] C / D 50 , C / D 10 , and C / D 90 is the ratio of particle size distribution to average pore size. The size of the pore size corresponds to the size of the reaction site. C / D 50 , C / D 10 , and C / D 90 The CAM produced by using as a raw material a precursor in which at least one of the above is equal to or greater than the lower limit has sufficient reaction sites. In such a CAM, lithium ions are likely to diffuse during charging and discharging, i.e., the internal resistance is likely to be low. Therefore, the discharge rate characteristics of the lithium secondary battery are likely to be improved.
[0058] C / D 50 , C / D 10 , and C / D 90 The CAM produced by using a precursor having at least one of the above values or less as a raw material does not have an excessive amount of reactive sites, and the electrolyte is less likely to decompose and generate gas during charging and discharging, which can improve the initial charge and discharge efficiency.
[0059] The BET specific surface area of the precursor is 25m 2 / g or more is preferable, and 30m 2 / g or more is more preferable, and 40m 2 The BET specific surface area of the precursor is preferably 100 m 2 / g or less is preferable, and 90m 2 / g or less is more preferable, and 80m 2 The BET specific surface area of the precursor is preferably 25 to 100 m 2 / g is preferable, and 30 to 90m 2 / g is more preferable, and 40 to 80m 2 / g is more preferred.
[0060] When the BET specific surface area of the precursor is equal to or greater than the lower limit, in a lithium secondary battery using the CAM obtained by using the precursor as a positive electrode, the contact area between the CAM and the electrolyte is ensured, and thus lithium ions are likely to diffuse during charging and discharging, i.e., the internal resistance is likely to be low. Therefore, the discharge rate characteristics of the lithium secondary battery are likely to be improved. In addition, when the BET specific surface area of the precursor is equal to or less than the upper limit, in a lithium secondary battery using the obtained CAM as a positive electrode, the contact area between the CAM and the electrolyte is unlikely to increase, and gas generation due to decomposition of the electrolyte is likely to be suppressed. As a result, the initial charge / discharge efficiency can be improved.
[0061] The average pore size C of the precursor is preferably 8 nm or more, and more preferably 10 nm or more. C is preferably 20 nm or less, more preferably 18 nm or less, and even more preferably 15 nm or less. C is preferably 8 to 20 nm, more preferably 8 to 18 nm, even more preferably 8 to 15 nm, and particularly preferably 10 to 15 nm.
[0062] The CAM produced by using a precursor having C equal to or greater than the lower limit as a raw material has sufficient reaction sites. In such a CAM, lithium ions are easily diffused during charging and discharging, that is, the internal resistance is easily reduced. Therefore, the discharge rate characteristics of the lithium secondary battery are easily improved.
[0063] A CAM prepared by using a precursor having a C content equal to or less than the upper limit as a raw material does not have an excessive amount of reactive sites, and the electrolyte is less likely to decompose and generate gas during charging and discharging, which can improve the initial charge / discharge efficiency.
[0064] Precursor D 50 is preferably 10 μm, more preferably 11 μm, and even more preferably 12 μm. 50 is preferably 20 μm, more preferably 18 μm, and even more preferably 15 μm. 50 The thickness is preferably from 10 to 20 μm, more preferably from 11 to 18 μm, and even more preferably from 12 to 15 μm.
[0065] Precursor D 50 When 50 is within the above range, when manufacturing a positive electrode using the CAM obtained using the precursor, it becomes easier to densely fill the CAM in the positive electrode active material layer. As a result, the contact between the CAM and the conductive auxiliary agent becomes good, and a positive electrode with low resistance can be manufactured. In addition, since side reactions during charge and discharge are less likely to occur, a high capacity can be obtained even at a large discharge rate, and the discharge rate characteristics can be improved.
[0066] The precursor preferably satisfies the following (I). Ni:Co:M1 = (1 - y - z):y:z ···(I) (M1 is the above-mentioned element M1. The formula (I) satisfies 0 ≦ y ≦ 0.4, 0 ≦ z ≦ 0.5, and 0 < y + z.)
[0067] (y) y preferably satisfies 0 ≦ y ≦ 0.1.
[0068] (z) z is preferably 0.01 or more, more preferably 0.02 or more, and even more preferably 0.03 or more. Also, z is preferably 0.44 or less, more preferably 0.42 or less, and even more preferably 0.40 or less.
[0069] z preferably satisfies 0.01 ≦ z ≦ 0.44, more preferably 0.02 ≦ z ≦ 0.42, and even more preferably 0.03 ≦ z ≦ 0.40.
[0070] (y + z) From the viewpoint of improving the discharge rate characteristics and the initial charge-discharge efficiency, y + z is preferably 0.5 or less, more preferably 0.3 or less, and even more preferably 0.2 or less. y + z preferably satisfies 0 < y + z ≦ 0.5, more preferably 0 < y + z ≦ 0.3, and even more preferably 0 < y + z ≦ 0.2.
[0071] The precursor is preferably represented by the following formula (I)-1. Ni (1-y-z) Co y M1z O x Formula (I)-1
[0072] In formula (I)-1, the explanations for M1, y and z are the same as those for M1, y and z in (I) above.
[0073] (x) x is preferably 0.02 or more, more preferably 0.03 or more, and even more preferably 0.05 or more. x is preferably 2.8 or less, more preferably 2.6 or less, and even more preferably 2.4 or less.
[0074] x preferably satisfies 0≦x≦2.8, more preferably satisfies 0.02≦x≦2.8, further preferably satisfies 0.03≦x≦2.6, and particularly preferably satisfies 0.05≦x≦2.4.
[0075] <Precursor manufacturing method> The method for producing the precursor includes a step of obtaining a metal composite hydroxide containing at least Ni and one or more elements selected from the group consisting of Co and element M1, and an oxidation step of heating the metal composite hydroxide.
[0076] [Step of obtaining metal composite hydroxide] First, a metal composite hydroxide containing Ni and one or more elements selected from the group consisting of Co and element M1 is prepared. The metal composite hydroxide can be produced by a batch co-precipitation method or a continuous co-precipitation method.
[0077] Specifically, by a continuous coprecipitation method, a first metal salt solution containing Ni as a main component, a second metal salt solution containing one or more elements selected from the group consisting of Co and element M1 as a main component, and an alkaline aqueous solution are supplied to a reaction vessel and reacted to produce Ni. (1-y-z) Co y M1 z A metal composite hydroxide represented by (OH)2 (y and z are the same as y and z in (I) above) is produced. Here, "containing Ni as a main component" means that the content of Ni relative to the total amount of metal elements contained in the first metal salt solution is 70 mass% or more. "containing one or more elements selected from the group consisting of Co and element M1 as a main component" means that the content of one or more elements selected from the group consisting of Co and element M1 relative to the total amount of metal elements contained in the second metal salt solution is 70 mass% or more. However, the first aqueous solution may contain Co or element M1 as long as the above content is satisfied. The second aqueous solution may also contain Ni as long as the above content is satisfied.
[0078] The first metal salt solution includes a nickel salt solution. As the nickel salt that is a solute of the nickel salt solution, for example, at least one of nickel sulfate, nickel nitrate, nickel chloride, and nickel acetate can be used.
[0079] The second metal salt solution includes at least one of a cobalt salt solution and a metal salt solution of element M1. As the cobalt salt, which is a solute of the cobalt salt solution, for example, at least one of cobalt sulfate, cobalt nitrate, cobalt chloride, and cobalt acetate can be used.
[0080] As the metal salt of element M1 which is the solute of the metal salt solution of element M1, for example, manganese sulfate, manganese nitrate, manganese chloride, manganese acetate, aluminum sulfate, sodium aluminate, etc. can be used.
[0081] The amount of each metal salt is specified so that the molar ratio of Ni, Co, and element M1 in the mixed solution containing the metal salts corresponds to (1-yz):y:z in the above formula (I). Water is used as the solvent.
[0082] In the coprecipitation method, in order to adjust the pH of the mixture of the first metal salt solution and the second metal salt solution, an alkaline aqueous solution is supplied to the mixture before the pH of the mixture changes from alkaline to neutral. An example of the alkaline aqueous solution is a sodium hydroxide aqueous solution.
[0083] The ratio (S1 / S2) of the supply amount S1 (unit: L / min) of the second metal salt solution supplied to the reaction tank to the supply amount (unit: L / min) of the alkaline aqueous solution supplied to the reaction tank is set to 0.05 to 0.10. This makes it easier to obtain a precursor that satisfies the above (1) by growing crystals biased toward a specific plane.
[0084] The second metal salt solution may be supplied to the reaction tank from multiple supply ports. When the second metal salt solution is supplied from multiple supply ports, the total amount of the second metal salt solution at each supply port corresponds to the above S1. When multiple types of second metal salt solutions are used, the total amount of each second metal salt solution supplied corresponds to the above S1. Similarly, the aqueous alkaline solution may be supplied to the reaction tank from a plurality of supply ports. When the aqueous alkaline solution is supplied from a plurality of supply ports, the total amount of the aqueous alkaline solution at each supply port corresponds to S2 above.
[0085] In the manufacturing process of the metal composite hydroxide, a complexing agent may be used. That is, the mixed solution may contain a complexing agent. The complexing agent is capable of forming a complex with nickel ions, cobalt ions, and manganese ions in an aqueous solution, and examples of the complexing agent include ammonium ion donors (ammonium hydroxide, ammonium sulfate, ammonium chloride, ammonium carbonate, ammonium fluoride, etc.), hydrazine, ethylenediaminetetraacetic acid, nitrilotriacetic acid, uracil diacetic acid, and glycine.
[0086] When a complexing agent is used, the amount of the complexing agent contained in the first metal salt solution, the second metal salt solution, and the mixed liquid containing the complexing agent is, for example, a molar ratio of the amount of the complexing agent to the total number of moles of the metal salts (nickel salt, cobalt salt, and metal salt of element M1) that is greater than 0 and less than or equal to 2.0.
[0087] During the reaction, the temperature of the reaction vessel is controlled within a range of preferably 50 to 80° C., more preferably 60 to 70° C. This allows the crystals to grow biasedly in a specific plane direction, and a precursor that satisfies the above (1) is obtained.
[0088] The pH of the mixed liquid in the reaction tank is preferably 9 to 13. The pH value in the reaction tank is measured when the temperature of the mixed liquid is 40°C.
[0089] The reaction precipitate formed in the reaction tank is neutralized with stirring. The neutralization time of the reaction precipitate is, for example, 1 to 20 hours.
[0090] The reaction vessel used in the continuous coprecipitation method may be an overflow type reaction vessel for separating the reaction precipitate formed.
[0091] When producing a metal composite hydroxide by a batch coprecipitation method, examples of the reaction tank include a reaction tank that is not equipped with an overflow pipe, and an apparatus that has a mechanism for concentrating the overflowed reaction precipitate in a concentration tank connected to an overflow pipe and circulating it back to the reaction tank.
[0092] It is preferable to supply an inert gas into the reaction vessel, and various gases, for example, nitrogen, argon, or a mixture thereof, are supplied into the reaction vessel.
[0093] By appropriately controlling S1 / S2, the temperature of the reaction vessel, the pH of the mixture in the reaction vessel, etc., the D 50 and C / D 50 can be controlled within the above range.
[0094] After the above reaction, the neutralized reaction precipitate is washed and isolated, for example by dehydrating the slurry containing the reaction precipitate by centrifugation or suction filtration.
[0095] The reaction precipitate is preferably washed with water or an alkaline washing solution. In this embodiment, washing with an alkaline washing solution is preferred, and washing with an aqueous sodium hydroxide solution is more preferred.
[0096] After isolation, the mixture is dried and sieved as necessary to obtain a metal composite hydroxide.
[0097] [Oxidation process] The metal composite hydroxide is heated to obtain the above-mentioned precursor, which is a metal composite oxide. The heating time is preferably 1 to 30 hours in total from the start of temperature increase to the end of temperature retention after reaching the maximum retention temperature. The temperature increase rate in the heating step to reach the maximum retention temperature is preferably 180°C / hour or more, more preferably 200°C / hour or more, and even more preferably 250°C / hour or more.
[0098] The maximum holding temperature in this specification refers to the maximum holding temperature of the atmosphere inside the apparatus used in the oxidation step.
[0099] The temperature rise rate in this specification is calculated from the time from the start of temperature rise to the time when the maximum holding temperature is reached and the temperature difference from the temperature at the start of temperature rise to the maximum holding temperature.
[0100] The maximum holding temperature is preferably from 500 to 750°C, and more preferably from 550 to 700°C. When the maximum holding temperature is equal to or higher than the lower limit, the metal composite hydroxide is sufficiently oxidized, and it is easy to obtain a precursor that satisfies the above condition (2). By setting the maximum holding temperature within the above range, the C / D ratio of the precursor can be reduced. 50 , C / D 10 , C / D 90 , the BET specific surface area, and the above C can be adjusted to fall within the above-mentioned ranges.
[0101] The metal composite hydroxide is placed in a heating container such as a sheath box, and the temperature is raised to the above-mentioned maximum holding temperature in an air atmosphere. At this time, it is preferable to adjust the total flow rate (unit: L) of air supplied from the start of temperature increase until the maximum holding temperature is reached and before temperature decrease starts so as to satisfy the following (A). (A) 0.009mm / L≦thickness of metal complex hydroxide layer (unit: mm) / total flow rate of air supplied from the start of heating until the maximum holding temperature is reached and before the temperature starts to decrease (unit: L)≦0.15mm / L
[0102] The layer thickness of the metal composite hydroxide in (A) above is the thickness of the powder layer of the metal composite hydroxide contained in a heating container. The thickness of the powder layer is the height from the inner bottom of the container in contact with the metal composite hydroxide to the surface of the powder layer of the metal composite hydroxide contained in the container.
[0103] By controlling the powder layer thickness and the total air flow rate, it is possible to control the loss of moisture from the powder layer. By adjusting the metal composite hydroxide layer thickness and air flow rate to satisfy the above condition (A), it is possible to reduce the occurrence of uneven oxidation, reduce excess moisture in the powder layer, and suppress the aggregation of particles, making it easier to obtain a precursor that satisfies the desired pore state. By decreasing the value of "metal composite hydroxide layer thickness (unit: mm) / total air flow rate supplied from the start of heating until the maximum holding temperature is reached and before cooling begins," the total pore volume of the obtained precursor tends to increase.
[0104] The oxidation step may be performed using either a stationary calciner or a fluidized calciner. As the stationary firing furnace, an oxidizing atmosphere firing furnace, a roller hearth kiln, a shuttle kiln, a pusher kiln, or a batch firing furnace can be used. As the fluidized firing furnace, for example, a rotary kiln can be used.
[0105] By raising the temperature under the condition that satisfies the above (A), the moisture and surface carbon contained in the metal composite hydroxide are easily removed, and the removed traces become pores, making it easy to obtain a precursor that satisfies the above (1).
[0106] After reaching the maximum holding temperature, the temperature is lowered from the maximum holding temperature to room temperature in an air atmosphere. At this time, the total flow rate (unit: L) of air supplied from the start of the temperature drop to the time when room temperature is reached is adjusted so as to satisfy (B) below. (B) 0.009mm / L≦powder layer thickness in the container (unit: mm) / total flow rate of air supplied from the start of cooling until reaching room temperature (unit: L)≦0.15mm / L
[0107] The layer thickness of the powder in the container in (B) above is the thickness of the powder layer contained in the heating container. Specifically, the thickness of the powder layer is the height from the inner bottom of the container in contact with the powder to the surface of the powder layer contained in the container.
[0108] By lowering the temperature under the condition that satisfies the above condition (B), the carbon dioxide components contained in the air atmosphere are less likely to be adsorbed onto the surface or pores of the powder in the container during the temperature lowering process, making it easier to obtain a precursor that satisfies the above condition (1).
[0109] By carrying out the process under conditions that satisfy the above (A) and (B), the C / D 50 , C / D 10 , C / D 90 , BET specific surface area, C, and D 50 can be adjusted to the above range.
[0110] By the above steps, the precursor can be produced.
[0111] <Method of manufacturing positive electrode active material for lithium secondary battery> The precursor can be used as a raw material to produce CAM. The method for producing CAM includes a calcination step of calcining a mixture of the precursor and a lithium compound.
[0112] [Mixing process] Before the firing step, a mixing step of mixing the precursor and a lithium compound may be carried out. As the lithium compound, one or more compounds selected from the group consisting of lithium carbonate, lithium hydroxide, and lithium hydroxide monohydrate can be used.
[0113] The lithium compound and the precursor are mixed in consideration of the composition ratio of the final target product to obtain a mixture of the lithium compound and the precursor. The amount (molar ratio) of Li relative to the total amount of metal elements contained in the precursor, 1, is preferably 0.98 to 1.20, more preferably 1.01 to 1.10.
[0114] [Firing process] The resulting mixture is fired to grow CAM crystals.
[0115] The firing temperature in this specification means the temperature of the atmosphere in the firing furnace, and refers to the maximum temperature that can be maintained (maximum maintenance temperature). When the firing process has a plurality of firing stages, the firing temperature means the temperature of the stage in which firing is performed at the highest holding temperature among the firing stages.
[0116] The firing temperature is preferably from 500 to 1000°C, more preferably from 550 to 980°C, and further preferably from 600 to 960°C.
[0117] The time for which the material is held at the calcination temperature is preferably 0.1 to 20 hours, more preferably 0.5 to 10 hours. The apparatus used in the calcination step may be a stationary calcination furnace or a fluidized calcination furnace.
[0118] It is also preferable to carry out the calcination in an oxygen-containing atmosphere. Specifically, it is preferable to introduce oxygen gas into the calcination furnace to create an oxygen-containing atmosphere.
[0119] The fired product obtained in the firing step is appropriately pulverized and sieved to obtain CAM.
[0120] By using the above precursor as a raw material for CAM, it is possible to manufacture a lithium secondary battery that has excellent discharge rate characteristics and exhibits high initial charge / discharge efficiency.
[0121] Although the preferred embodiment of the present invention has been described above, the present invention is not limited to the above embodiment. The shapes and combinations of the components shown in the above embodiment are merely examples, and various modifications can be made based on design requirements, etc., without departing from the spirit of the present invention.
[0122] <Lithium secondary battery> A positive electrode for a lithium secondary battery suitable for use with the CAM of this embodiment will be described below. Hereinafter, the positive electrode for a lithium secondary battery may be referred to as a positive electrode. Furthermore, a lithium secondary battery suitable for use as a positive electrode will be described.
[0123] An example of a suitable lithium secondary battery for use with the CAM of this embodiment has a positive electrode, a negative electrode, a separator sandwiched between the positive electrode and the negative electrode, and an electrolyte solution disposed between the positive electrode and the negative electrode.
[0124] 1 is a schematic diagram showing an example of a lithium secondary battery. For example, a cylindrical lithium secondary battery 10 is manufactured as follows.
[0125] First, as shown in the partially enlarged view of FIG. 1 , a pair of strip-shaped separators 1, a strip-shaped positive electrode 2 having a positive electrode lead 21 at one end, and a strip-shaped negative electrode 3 having a negative electrode lead 31 at one end are laminated in the order of separator 1, positive electrode 2, separator 1, and negative electrode 3, and then wound to form an electrode group 4.
[0126] The positive electrode 2, for example, has a positive electrode active material layer 2a containing CAM, and a positive electrode current collector 2b on one surface of which the positive electrode active material layer 2a is formed. Such a positive electrode 2 can be manufactured by first preparing a positive electrode mixture containing CAM, a conductive material, and a binder, and supporting the positive electrode mixture on one surface of the positive electrode current collector 2b to form the positive electrode active material layer 2a.
[0127] Examples of the negative electrode 3 include an electrode in which a negative electrode mixture containing a negative electrode active material (not shown) is supported on a negative electrode current collector, and an electrode made of only the negative electrode active material. The negative electrode 3 can be manufactured in a manner similar to that for the positive electrode 2.
[0128] Next, the electrode group 4 and an insulator (not shown) are housed in the battery can 5, the bottom of the can is sealed, the electrode group 4 is impregnated with an electrolyte solution 6, and the electrolyte is disposed between the positive electrode 2 and the negative electrode 3. Furthermore, the upper part of the battery can 5 is sealed with a top insulator 7 and a sealing body 8, whereby a lithium secondary battery 10 can be manufactured.
[0129] The shape of the electrode group 4 can be, for example, a columnar shape such that the cross-sectional shape when the electrode group 4 is cut perpendicular to the winding axis is a circle, an ellipse, a rectangle, or a rectangle with rounded corners.
[0130] The shape of a lithium secondary battery having such an electrode group 4 can be any shape defined by IEC60086, which is a standard for batteries defined by the International Electrotechnical Commission (IEC), or JIS C 8500. For example, cylindrical or rectangular shapes can be used.
[0131] Furthermore, the lithium secondary battery is not limited to the above-mentioned wound type configuration, and may be a laminated type configuration in which a laminated structure of a positive electrode, a separator, a negative electrode, and a separator is repeatedly stacked. Examples of the laminated type lithium secondary battery include a so-called coin type battery, a button type battery, and a paper type (or sheet type) battery.
[0132] For the positive electrode, separator, negative electrode, and electrolyte constituting the lithium secondary battery, for example, the configurations, materials, and manufacturing methods described in
[0113] to
[0140] of WO2022 / 113904A1 can be used.
[0133] <All-solid-state lithium secondary battery> The CAM of this embodiment can be used as a CAM for an all-solid-state lithium secondary battery.
[0134] Fig. 2 is a schematic diagram showing an example of an all-solid-state lithium secondary battery. The all-solid-state lithium secondary battery 1000 shown in Fig. 2 has a laminate 100 having a positive electrode 110, a negative electrode 120, and a solid electrolyte layer 130, and an exterior body 200 that houses the laminate 100. The all-solid-state lithium secondary battery 1000 may also have a bipolar structure in which a CAM and a negative electrode active material are arranged on both sides of a current collector. A specific example of the bipolar structure is the structure described in JP-A-2004-95400.
[0135] The positive electrode 110 has a positive electrode active material layer 111 and a positive electrode current collector 112. The positive electrode active material layer 111 contains the above-mentioned CAM and a solid electrolyte. The positive electrode active material layer 111 may also contain a conductive material and a binder.
[0136] The negative electrode 120 has a negative electrode active material layer 121 and a negative electrode current collector 122. The negative electrode active material layer 121 contains a negative electrode active material. The negative electrode active material layer 121 may also contain a solid electrolyte and a conductive material.
[0137] The laminate 100 may have an external terminal 113 connected to the positive electrode current collector 112 and an external terminal 123 connected to the negative electrode current collector 122. In addition, the all-solid-state lithium secondary battery 1000 may have a separator between the positive electrode 110 and the negative electrode 120.
[0138] The all-solid-state lithium secondary battery 1000 further includes an insulator (not shown) that insulates the laminate 100 from the exterior body 200 , and a sealing body (not shown) that seals the opening 200 a of the exterior body 200 .
[0139] A container molded from a highly corrosion-resistant metal material such as aluminum, stainless steel, or nickel-plated steel can be used as the exterior body 200. Also, a container formed into a bag shape from a laminate film having at least one surface treated to be corrosion-resistant can be used as the exterior body 200.
[0140] Examples of the shape of the all-solid-state lithium secondary battery 1000 include a coin type, a button type, a paper type (or a sheet type), a cylindrical type, a square type, and a laminate type (pouch type).
[0141] The all-solid-state lithium secondary battery 1000 is illustrated as having one laminate 100 as an example, but the present embodiment is not limited to this. The all-solid-state lithium secondary battery 1000 may have a configuration in which the laminate 100 is used as a unit cell, and a plurality of unit cells (laminated bodies 100) are sealed inside an exterior body 200.
[0142] For the all-solid-state lithium secondary battery, for example, the configuration, materials, and manufacturing method described in
[0151] to
[0181] of WO2022 / 113904A1 can be used. EXAMPLES
[0143] <Method for measuring total pore volume> The total pore volume of the precursor was measured as described above in [Method of measuring total pore volume].
[0144] Using the method described in the above [Powder X-ray Diffraction Measurement], the precursors A and B were measured respectively, and A / B was calculated.
[0145] <C / D 50 , C / D 10 , and C / D 90 > The precursor C was measured by the above [Method for Measuring Average Pore Diameter]. The precursor D 10 , D 50 and D 90 were measured as described in the above [Method for Measuring Particle Size Distribution]. From the obtained values, C / D 50 , C / D 10 , and C / D 90 were calculated respectively.
[0146] <Method for Measuring BET Specific Surface Area> The BET specific surface area of the precursor was measured as described in the above [Method for Measuring BET Specific Surface Area].
[0147] <Composition Analysis> The composition of the precursor was measured by the method described in the above [Composition Analysis].
[0148] <Method for Evaluating Precursor> As described in the above [Method for Evaluating Precursor], a lithium secondary battery was manufactured, and the 1CA / 0.2CA discharge capacity ratio and the initial charge-discharge efficiency were measured.
[0149] (Example 1) After adding water into a reaction tank equipped with a stirrer and an overflow pipe, an aqueous sodium hydroxide solution was added, and the liquid temperature was maintained at 70 °C.
[0150] An aqueous nickel sulfate solution and an aqueous cobalt sulfate solution were mixed to prepare a first metal salt solution. Also, an aqueous aluminum sulfate solution was prepared as a second metal salt solution. The first metal salt solution and the second metal salt solution were continuously supplied to the reaction tank at a ratio such that the molar ratio of Ni, Co, and Al was 0.88:0.09:0.03.
[0151] At the same time, an aqueous solution of ammonium sulfate was supplied as a complexing agent into the reaction tank, and an aqueous solution of sodium hydroxide was supplied as an alkaline aqueous solution. At this time, the ratio (S1 / S2) of the supply amount S1 of the second metal salt solution to the supply amount S2 of the alkaline aqueous solution was adjusted to 0.08. At this time, the pH of the mixed solution in the reaction tank was 11.51 (measurement temperature: 40°C).
[0152] The obtained reaction precipitate 1 was washed, dehydrated, dried and sieved to obtain a metal composite hydroxide 1 containing Ni, Co and Al.
[0153] Next, 200 g of the metal composite hydroxide 1 was placed in a square sheath box having an inner dimension of 120 mm×120 mm and a height of 60 mm, and the layer thickness of the metal composite hydroxide 1 was set to 21 mm. The sheath box containing the metal composite hydroxide 1 was placed in an oxidizing atmosphere firing furnace (manufactured by Motoyama Corporation, product name: SKA-3050F-SP) and heated to 500° C. in an air atmosphere. At this time, the total flow rate of air supplied from the start of the temperature increase until the maximum held temperature is reached and the temperature decrease starts was 300 L, that is, the layer thickness of metal composite hydroxide 1 / total flow rate of air supplied from the start of the temperature increase until the maximum held temperature is reached and the temperature decrease starts (in Table 1, this is indicated as "layer thickness of metal composite hydroxide / total flow rate of air") was 0.070 mm / L. After the temperature was increased, the temperature was maintained at 500° C. and heating was continued for 5 hours.
[0154] Next, the temperature was lowered from 500° C. to room temperature in an air atmosphere. At this time, the total flow rate of air supplied from the start of the temperature drop until room temperature was reached was 300 L, that is, the powder layer thickness in the sheath box (container) / total flow rate of air supplied from the start of the temperature drop until room temperature was reached (in Table 1, this is written as "powder layer thickness in container / total flow rate of air") was 0.070 mm / L. This gave precursor 1.
[0155] (Examples 2 to 5) Precursors 2 to 5 were obtained in the same manner as in Example 1, except that the conditions in the oxidation step were changed as shown in Table 1.
[0156] Comparative Example 1 Metal composite hydroxide 1 was used as precursor C1 as it was.
[0157] (Comparative Examples 2 to 4) Precursors C2 to C4 were obtained in the same manner as in Example 1, except that the conditions in the oxidation step were changed as shown in Table 1.
[0158] Comparative Example 5 Precursor C5 was obtained in the same manner as in Example 1, except that 40 g of metal composite hydroxide 1 was placed in a square sheath having an inner dimension of 120 mm × 120 mm and a height of 60 mm, the layer thickness of metal composite hydroxide 1 was set to 4.2 mm, and the conditions in the oxidation step were changed as shown in Table 1.
[0159] Comparative Example 6 Metal composite hydroxide 2 containing Ni, Co, and Al was obtained in the same manner as in Example 1, except that S1 / S2 was set to 0.13 and the pH of the mixed solution in the reaction tank was changed to 12.1 (measurement temperature: 40° C.). Metal composite hydroxide 2 was used as precursor C6.
[0160] Comparative Example 7 Precursor C7 was obtained in the same manner as in Example 1, except that 250 g of metal composite hydroxide 2 was placed in a square sheath having an inner dimension of 120 mm × 120 mm and a height of 60 mm, the layer thickness of metal composite hydroxide 2 was set to 21 mm, and the conditions in the oxidation step were changed as shown in Table 1.
[0161] The compositions of precursors 1 to 5 obtained in Examples 1 to 5 and precursors C1 to C7 obtained in Comparative Examples 1 to 7 all had y=0.09 and z=0.03, corresponding to the above formula (I).
[0162] For the precursors 1 to 5 obtained in Examples 1 to 5 and the precursors C1 to C7 obtained in Comparative Examples 1 to 7, CAMs were produced by the following method. Lithium hydroxide was weighed out so that the amount (molar ratio) of Li was 1.02 relative to the total amount of Ni, Co, and Al contained in the precursor, which was 1. The precursor and lithium hydroxide were mixed to obtain a mixture.
[0163] This mixture was placed in an oxidizing atmosphere firing furnace (manufactured by Motoyama Corporation, product name: SKA-3050F-SP) and subjected to primary firing at 650° C. for a holding time of 5 hours.
[0164] After the primary firing, the mixture was placed in an oxidizing atmosphere firing furnace (manufactured by Motoyama Corporation, product name: SKA-3050F-SP) and subjected to secondary firing at 740°C for a holding time of 5 hours to obtain a fired product.
[0165] The fired product was mixed with pure water whose temperature was adjusted to 5° C. in such a ratio that the weight ratio of the fired product to the total amount was 50 mass % to prepare a slurry. The slurry was stirred for 20 minutes, washed, dehydrated, and heat-treated at 210° C. for 10 hours in a nitrogen atmosphere. This resulted in the CAM.
[0166] Table 1 shows the production conditions for Examples 1 to 5 and Comparative Examples 1 to 7.
[0167] [Table 1]
[0168] Table 2 shows the physical properties of the precursors of Examples 1 to 5 and Comparative Examples 1 to 7, the 1CA / 0.2CA discharge capacity ratio, and the initial charge / discharge efficiency. [Table 2]
[0169] The results shown in Table 2 indicate that the lithium secondary battery using the CAM produced using the precursor satisfying the above (1) and (2) as a raw material had excellent discharge rate characteristics and initial charge / discharge efficiency.
[0170] In contrast, in Comparative Example 1, as well as Comparative Examples 2 to 4 and 6, either or both of the discharge rate characteristics and the initial charge / discharge efficiency were lower than those of the Examples. This is believed to be because the metal composite hydroxide and the metal composite oxide were mixed together due to the metal composite hydroxide remaining as it is or being insufficiently oxidized, and crystals into which lithium ions can easily diffuse were not formed, resulting in an increase in internal resistance.
[0171] In Comparative Example 5, the discharge rate characteristics and the initial charge-discharge efficiency were lower than those of the Examples. This is believed to be because the conditions (A) and (B) above were not satisfied, and therefore water was not sufficiently removed from the metal composite hydroxide in the oxidation step, and pores were not sufficiently formed.
[0172] The initial charge-discharge efficiency of Comparative Example 7 was lower than that of Examples. This is believed to be because S1 / S2 was 0.13, and therefore the precursor crystals could not grow biasedly in a specific plane direction. [Explanation of symbols]
[0173] 1: separator, 2: positive electrode, 2a: positive electrode active material layer, 2b: positive electrode current collector layer, 3: negative electrode, 4: electrode group, 5: battery can, 6: electrolyte, 7: top insulator, 8: sealing body, 10: lithium secondary battery, 21: positive electrode lead, 31: negative electrode lead, 100: laminate, 110: positive electrode, 111: positive electrode active material layer, 112: positive electrode current collector, 113: external terminal, 120: negative electrode, 121: negative electrode active material layer, 122: negative electrode current collector, 123: external terminal, 130: solid electrolyte layer, 200: exterior body, 200a: opening, 1000: all-solid-state lithium secondary battery
Claims
1. A precursor for a positive electrode active material for a lithium secondary battery, the precursor containing at least Ni and one or more elements selected from the group consisting of Co and element M1, and satisfying the following (1) and (2): (1) In the pore size distribution calculated from the nitrogen adsorption isotherm by the Barrett-Joyner-Halenda (BJH) method, the total pore volume in the pore size range of 2 nm to 200 nm is 0.115 cm 3 / g or more 0.180cm 3 / g or less. (2) 0.84<A / B<0.95 (A is the half-width of a diffraction peak present within the range of 2θ=37.5±1° in powder X-ray diffraction measurement using a CuKα radiation source, and B is the half-width of a diffraction peak present within the range of 2θ=43.5±1°.)
2. The precursor according to claim 1 , which satisfies the following (3): (3)0.6×10 -3 ≦C / D 50 ≦1.6×10 -3 (C is the average pore diameter (nm) in the pore diameter distribution, and D 50 is the 50% cumulative volume particle size (μm) obtained from a volume-based cumulative particle size distribution curve measured by a laser diffraction scattering method.
3. The precursor according to claim 1 or 2, which satisfies the following (4). (4)1.0×10 -3 ≦C / D 10 ≦2.5×10 -3 (C is the average pore diameter (nm) in the pore diameter distribution, and D 10 is the 10% cumulative volume particle size (μm) obtained from a volume-based cumulative particle size distribution curve measured by a laser diffraction scattering method.
4. The precursor according to claim 1 or 2, which satisfies the following (5). (5)0.4×10 -3 ≦C / D 90 ≦1.0×10 -3 (C is the average pore diameter (nm) in the pore diameter distribution, and D 90 is the 90% cumulative volume particle size (μm) obtained from a volume-based cumulative particle size distribution curve measured by a laser diffraction scattering method.
5. BET specific surface area is 25m 2 / g or more 100m 2 The precursor according to claim 1 or 2, wherein the molecular weight is 0.1 to 0.5 μm.
6. 3. The precursor according to claim 1, wherein C, the average pore diameter in the pore diameter distribution, is 8 nm or more and 20 nm or less.
7. D is the 50% cumulative volume particle size obtained from a volume-based cumulative particle size distribution curve measured by a laser diffraction scattering method. 50 The precursor according to claim 1 or 2, wherein the thickness of the first layer is 10 μm or more and 20 μm or less.
8. 3. The precursor according to claim 1 or 2, which satisfies the following formula (I): Ni:Co:M1=(1-y-z):y:z...(I) (M1 is one or more elements selected from the group consisting of Mn, Mg, Ca, Sr, Ba, Zn, B, Al, Ga, Ti, Zr, Ge, Fe, Cu, Cr, V, W, Mo, Sc, Y, Nb, La, Ta, Tc, Ru, Rh, Pd, Ag, Cd, In, and Sn. Formula (I) satisfies 0≦y≦0.4, 0≦z≦0.5, and 0<y+z.)
9. A method for producing a positive electrode active material for a lithium secondary battery, comprising the step of firing a mixture of the precursor according to claim 1 or 2 and a lithium compound.
Citation Information
Patent Citations
Positive electrode active material for nonaqueous electrolyte secondary battery, manufacturing method, and nonaqueous electrolyte secondary battery using the same
JP2010015959A